Dynamics Analysis for Planar Mechanical System with Joint Lubricated - Shi Ping; Bai Yaqiong (Jixie chuandong)
Under the condition of considering joint clearance and lubrication,the dynamics performance analysis of mechanical system is carried out. For the case of the joints with clearance model as a contact pair with dry contact,based on the Lankarani- Nikravesh contact force model,the normal contact force model between the elements of clearance joint is built,the friction forces are calculated by using a modified Coulomb friction model. For the lubricated case,the hydrodynamic theory for dynamics is used to compute the fluid pressure based on Reynolds equation. Subsequently,the dynamics model of mechanical system with joint lubrication is established via the equations of motion for multi- body systems. The slider- crank mechanism is taken as an example to compare the dynamic performance of this mechanism in the case of with lubricated model and without lubricated model. The numerical results point out that the performance of this mechanism with lubricated joint is closer to that of an ideal joint.